Current knowledge and future perspectives on acute hepatitis C infection. (August 2015) - Hullegie, S.J.; Arends, J.E.; Rijnders, B.J.A.; Irving, W.L.; Salmon, D.; Prins, M.; Wensing, A.M.; Klenerman, P.; Leblebicioglu, H.; Boesecke, C.; Rockstroh, J.K.; Hoepelman, A.I.M.
Abstract: Acute hepatitis C virus (HCV) infections are frequently seen worldwide in certain risk groups, with an annual incidence rate varying between 0.08% and 66%. Although this incidence is substantial, a delayed diagnosis during chronic infection is most often made in the absence of clinical symptoms in the acute phase of the infection. Currently used methods to diagnose acute HCV infection are IgG antibody seroconversion and repeated HCV RNA measurements, although no definitive diagnostic test is currently available. Progress in the field of adaptive and innate immune responses has aided both advances in the field of HCV vaccine development and a more basic understanding of viral persistence. The rapid changes in the treatment of chronic HCV infection will affect therapeutic regimens for acute HCV infection in the coming years, leading to shorter treatment courses and pegylated interferon-free modalities. This review gives an overview of the current knowledge and uncertainties, together with some future perspectives on acute hepatitis C epidemiology, virology, immunology, and treatment.